2015
DOI: 10.1007/s00204-015-1451-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular dopamine and alterations on dopamine transporter are related to reserpine toxicity in Caenorhabditis elegans

Abstract: Reserpine is used as an animal model of parkinsonism. We hypothesized that the involuntary movements induced by reserpine in rodents are induced by dopaminergic toxicity caused by extracellular dopamine accumulation. The present study tested the effects of reserpine on the dopaminergic system in Caenorhabditis elegans. Reserpine was toxic to worms (decreased the survival, food intake, development and changed egg laying and defecation cycles). In addition, reserpine increased the worms' locomotor rate on food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…We examined the DA neurons of multiple mutant swip-10 alleles crossed to BY250, a strain that stably expresses the integrated transcriptional fusion p dat-1 :: GFP ( vtIs7) ( Fig 1A ) [ 46 ]. We focused our evaluations on CEP DA neurons, and quantitatively evaluated degeneration by three distinct morphological assessments: 1) neurite truncations and breaks in GFP-labeled dendrites ( Fig 1B and 1C ), 2) shrunken cell soma ( Fig 1D ) and 3) missing cell soma ( Fig 1E ), as previously described [ 47 , 48 ]. From these categories, we also calculated an overall degeneration score where the appearance of any of the components qualifies an animal as displaying CEP degeneration [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We examined the DA neurons of multiple mutant swip-10 alleles crossed to BY250, a strain that stably expresses the integrated transcriptional fusion p dat-1 :: GFP ( vtIs7) ( Fig 1A ) [ 46 ]. We focused our evaluations on CEP DA neurons, and quantitatively evaluated degeneration by three distinct morphological assessments: 1) neurite truncations and breaks in GFP-labeled dendrites ( Fig 1B and 1C ), 2) shrunken cell soma ( Fig 1D ) and 3) missing cell soma ( Fig 1E ), as previously described [ 47 , 48 ]. From these categories, we also calculated an overall degeneration score where the appearance of any of the components qualifies an animal as displaying CEP degeneration [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…We focused our evaluations on CEP DA neurons, and quantitatively evaluated degeneration by three distinct morphological assessments: 1) neurite truncations and breaks in GFP-labeled dendrites ( Fig 1B and 1C ), 2) shrunken cell soma ( Fig 1D ) and 3) missing cell soma ( Fig 1E ), as previously described [ 47 , 48 ]. From these categories, we also calculated an overall degeneration score where the appearance of any of the components qualifies an animal as displaying CEP degeneration [ 48 ]. We found that all three available swip-10 alleles ( vt29 and vt33 from our forward genetic screen, and the larger deletion allele, tm5915 ) exhibited elevations in the degeneration index, relative to wildtype animals ( Fig 1F–1I ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few publications measuring neurotransmitters in brain microdialysates exist, including Suominen et al presenting LODs for DA and SRT analyzed by LC-ESI-MS/MS of 0.20 nM (3 fmol injected onto the column) and an LOQ of 0.5 nM for DA and 1 nM for SRT [16, 17, 43]. Due to the high sensitivity of the developed method (LOQ DA: 0.37 nM; LOQ SRT: 0.14 nM; summarized in Table 2), the number of requisite worms (L1 stage) could be reduced to about 2,000 per sample compared to other HPLC methods requiring hundreds of thousands worms (200,000 worms) per sample [34, 44, 45]. While several methods extracting neurotransmitters from brain tissue are often laborious due to pretreatment or derivatization steps [13, 18, 35, 46], we developed a fast and simple extraction protocol allowing high-throughput analyses.…”
Section: Discussionmentioning
confidence: 99%